Two-dimensional NMR investigation of a bent DNA fragment: assignment of the proton resonances and preliminary structure analysis. - Kintanar, A (1987)
The resonances of all the non-exchangeable protons (except 5'H and 5"H) of d(CGAAAAATCGG) + d(CCGATTTTTCG), a putatively bent DNA duplex, have been assigned using 1H two-dimensional nuclear magnetic resonance methods. The nuclear Overhauser effect data indicate an overall B-form structure for this double-helical DNA undecamer. However, several features of the NMR data such as some unusually weak C8/C6 proton to C1' proton NOE cross-peaks, the presence of relatively intense C2H to C1'H NOE cross-peaks, and unusual chemical shifts of some 2", 2', and 1' protons suggest a substantial perturbation of the helix structure at the junctions and along the length of the tract of A residues. These structural deviations are considered in terms of models of DNA bending.